2012
DOI: 10.14361/transcript.9783839418765
|View full text |Cite
|
Sign up to set email alerts
|

»Unsichtbare« Migration?

Abstract: Dieses Buch knüpft an Intersektionalitäts- und Transnationalitätsansätze an und untersucht die Konstitution von Migrationsprozessen sowie die Konstruktionen von Migrantinsein. Am Beispiel der Biographien von scheinbar privilegierten, »unsichtbaren« Migrantinnen finnischer Herkunft zeigt die biographieanalytische Studie, wie Migrationsprojekte und Subjektkonstruktionen mit biographischen Transformationsprozessen verwoben sind und wie diese zur Konstitution eines transnationalen Handlungs- und Zugehörigkeitsraum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…La décision d'immigrer temporairement n'est généralement pas une décision individuelle, mais est davantage, souvent, un projet familial 243 . Au Canada, on observe un système à deux vitesses en matière de regroupement familial : un travailleur peu qualifié ne pourra généralement pas se prévaloir de cette prérogative, contrairement au travailleur temporaire hautement qualifié qui pourra se faire accompagner de sa famille, pour autant qu'il démontre qu'il a la capacité financière de les prendre en charge 244 .…”
Section: Dunclassified
“…La décision d'immigrer temporairement n'est généralement pas une décision individuelle, mais est davantage, souvent, un projet familial 243 . Au Canada, on observe un système à deux vitesses en matière de regroupement familial : un travailleur peu qualifié ne pourra généralement pas se prévaloir de cette prérogative, contrairement au travailleur temporaire hautement qualifié qui pourra se faire accompagner de sa famille, pour autant qu'il démontre qu'il a la capacité financière de les prendre en charge 244 .…”
Section: Dunclassified
“…It provides a complex and differentiated analysis of transmigration processes that takes into account the social situation of migrants in the country of origin and the country of arrival, and can thus reconstruct the agency and positionings of these subjects in transnational fields. Recently, several studies have shown that the biographical approach opens up a new perspective for the investigation of transmigration and the constitution of transnational social spaces (Fürstenau, 2004;Kempf, 2013;Lutz, 2007;Ruokonen-Engler, 2005, 2012aSiouti, 2013). Through the narrative reconstruction of biographical processes and subject positions, it is possible to explain how agency gets constructed around transnational belongings and positionings as a result of the interplay between individual biographical resources and structural constraints, emerging through the interplay and intersections of a range of locations and dislocations in relation to gender, ethnicity, class and racialization.…”
Section: Biographical Research In Transnational Migration Contextsmentioning
confidence: 99%
“…Our methodological notes and the tool of 'doing biographical reflexivity' are grounded in our own research projects about transmigration processes in the European context. We both have a so-called 'migration background' (Migrationshintergund) and were forced to reflect methodologically our own biographical entanglements with migration while researching transnational social fields (see Ruokonen-Engler, 2012a;Siouti, 2013).…”
Section: Researching Transnational Religious Fundamentalismmentioning
confidence: 99%